Polyploid giant cancer cells and tumor budding: translation from basic research to clinical application - Huang, Peng; Wu, Rong; Yang, Zhimou; Li, Yuwei; Fei, Fei; Yu, Yongjun (Frontiers in Oncology, 2025)
Polyploid giant cancer cells (PGCCs) represent a distinct subpopulation of tumor cells characterized by enlarged or multiple nuclei and aneuploidy. PGCCs are products of genomic instability, possessing cancer stem cell properties and exhibiting significant resistance to radiotherapy and chemotherapy. They can generate highly invasive daughter cells through asymmetric division, exhibiting epithelial-mesenchymal transition characteristics, and facilitating tumor recurrence and metastasis. In vivo, PGCCs with daughter cells in tumor tissue can migrate and infiltrate into the forefront stroma to form tumor budding, which are closely related to solid tumor recurrence, metastasis, and drug resistance. Studies have shown that inhibiting sphingolipid enzyme acid ceramidase or regulating autophagy can reduce the production of PGCCs with daughter cells. Under appropriate induction conditions, PGCCs with daughter cells can be induced to differentiate into benign tissues such as adipocytes, chondrocytes, and osteocytes, inhibiting their malignant proliferation and invasive destruction. This study reviewed the recent research developments regarding PGCCs, mainly explored the endogenous mechanisms of PGCCs formation and their malignant phenotype, as well as the process of tumor budding formation in vivo and potential therapeutic strategies targeting PGCCs. The main novelty of this study lies in exploring the translation of PGCCs basic research into the clinical pathological prognostic role of tumor budding, which can reveal the potential mechanism of PGCCs/tumor budding formation at the molecular level, providing theoretical basis for prognosis assessment, monitoring of recurrence and metastasis risks, as well as improving drug resistance and targeted therapy in cancer patients.